Will Artificial Intelligence Take Over Human Writer? - Kojima, Atsuki (Science Insights, 2024)
Despite notable progressions in artificial intelligence (AI) technology, the imminent complete supplanting of human writers by AI is exceedingly improbable. Undoubtedly, AI is currently capable of producing texts that are only marginally cogent or even imitate specific writing styles by utilizing machine learning and algorithms. However, what distinguishes human writers is their capacity to imbue their works with ingenuity, sentimentality, and distinct viewpoints. Writing is more than simply assembling words; it is an authentic expression of oneself. In addition, human beings possess superior cognitive abilities such as critical thinking, intuition, and the capacity to comprehend intricate contexts beyond the current capabilities of any algorithm. However, who can say what the future may bring? It is not inconceivable that talent-matched AI writers will one day compose bestselling novels and award-winning articles alongside us humans.